STRONGLY) π- REGULAR RINGS RELATIVE TO RIGHT IDEAL) - Alkhatib, Abdulbaset; Aodeh, Mohammed; Hakmi, Hamza (Journal of natural sciences, life and applied sciences, 2020)
In this paper we study the notion of π- regular and strongly π- regular rings relative to right ideal. We provide several characterizations of this rings and study their properties. It is shown that every ring R is π- regular relative to any maximal right ideal of R . Also, we find necessary and sufficient conditions to be a ring R satisfies the d.c.c. on chains of the form Ra ⊇ Ra² ⊇ Λ relative to ideal for every a ∈ R . New results obtained include necessary and sufficient conditions for a ring to be π- regular, strongly π- regular and P- potent relative to right ideal.